Class Struggle in the Bolivarian Process: Workers' Control and Workers' Councils. (January 2017) - Azzellini, Dario
Workers' initiatives and government measures in Venezuela to increase workers' participation in the management of their companies sharply contrast with institutional actions that intend to inhibit and reduce such participation. Despite this, the movement for workers' control in Venezuela has grown in recent years and achieved some important victories in conflicts in state companies. Las iniciativas de los trabajadores y las medidas del gobierno en Venezuela para aumentar la participación de los trabajadores en la gestión de sus compañías están en fuerte contraposición con las acciones institucionales que pretenden inhibir y reducir esa participación. A pesar de esto, el movimiento por el control obrero en Venezuela ha crecido en los últimos años y ha logrado algunas victorias importantes en varios conflictos en las compañías estatales.